Pengaruh Kecurangan Laporan Keuangan, Kualitas Laba dan Komisaris Independen terhadap Nilai Perusahaan dengan Sustainability Disclosure sebagai Pemoderasi - Samosir, David Kiki Baringin MT; Tambun, Sihar; Pebriana, Hanny (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine the effect of financial statement fraud, earnings quality, and independent commissioners on firm value and to see the moderating role of sustainability disclosure in the relationship. Financial statement fraud and earnings quality are the main focus because both reflect the integrity of financial information conveyed to stakeholders. Meanwhile, the existence of independent commissioners is assumed to have a strong supervisory role in maintaining the quality of reporting and corporate governance, as well as the role of sustainability disclosure as a moderating variabel in strengthening or weakening the relationship. This study was conducted on the real estate sector listed on the Indonesia stock exchange (IDX) for the 2020 – 2023 period. The research method used is quantitative with moderated regression analysis techniques. The results of the study are expected to provide theoretical contributions to the literature on corporate governance and sustainability reporting and provide practical implications for regulators, investors and company management. It is also expected that sustainability disclosure can strengthen the influence of independent variabels on company value.